(untitled) (Proceedings of the International Conference on Social Sciences, 2020)
Abstract: Since June 4, 2019, the 30th anniversary of the June Fourth massacre, mass protests have erupted across Hong Kong and continued today. This paper chooses a representative activism organization namely Hong Kong Alliance (Hong Kong Alliance in Support of Patriotic Democratic Movements of China) and takes it as a lens to analyse and estimate the role and effect of digital technologies in influencing the political campaign in the digital age. Specifically, this paper employs the connective and collective action theory to analyse the organisation structure and the operation mode of Hong Kong Alliance, and focus on the digital storytelling strategy that Hong Kong Alliance employed. Furthermore, this paper also discusses the criteria for assessing digital movement purposed by Yana Breindl and find that the static evaluation criterion is not appropriate in the current digital space. On the contrary, a dynamic appraisal method which does not only assess the result but also consider the value of the process is in need.